Comparing the effects of hot compress and hot ginger compress on pain associated with breast engorgement - Maryam Monazzami; Sedigheh Yousefzadeh; Hasan Rakhshandeh; Habibollah Esmaily (Kashan University of Medical Sciences, 2021)
Background: Breast engorgement (BE) is a physiologic condition in the postpartum period characterized by painful swelling of the breasts. BE-associated pain is the second main cause of exclusive breastfeeding failure in the early weeks of childbirth. Objectives: This study aimed to compare the effects of hot compress and hot ginger compress on BE-associated pain. Methods: This randomized clinical trial was conducted in 2018 on 76 breastfeeding women with BE conveniently recruited from Imam Reza hospital, Mashhad, Iran. Participants were randomly allocated to a control group to receive hot compress (n = 38) and an intervention group to receive hot ginger compress (n = 38). Study intervention was implemented in both groups thrice daily for 2 consecutive days. A Visual Analog scale was used for the assessment of BE-associated pain before and after the study intervention. Data were analyzed using the Mann-Whitney U, the independent-samples t, the Wilcoxon, and the Chi-square tests as well as the analysis of covariance. Results: The mean score of BE-associated pain in the right and the left breasts significantly reduced by, respectively, 6.25 ± 1.76 and 6.06 ± 1.76 points in the intervention group (P < 0.05) and by 3.21 ± 1.02 and 3.48 ± 1.21 points in the control group (P > 0.05). The decreases in the mean scores of the right and the left BE-associated pain in the intervention group were significantly greater than the control group (P < 0.05). Conclusion: Hot ginger compress is more effective than hot compress in reducing BE-associated pain among breastfeeding women.